2012
DOI: 10.1007/s00128-012-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants (PCBs and DDTs) in European Conger Eel, Conger conger L., from the Ionian Sea (Mediterranean Sea)

Abstract: The present study provides novel data regarding levels of polychlorinated biphenyls (PCBs) and organochlorine pesticides (DDTs) in muscle tissue of European conger eel (Conger conger) from Ionian Sea (Mediterranean Sea). The mean concentration of PCBs (891 ng g(-1) lipid weight) was higher than those of DDTs (543 ng g(-1) lipid weight). PCB pattern was dominated by higher chlorinated congeners (hexa-CBs: 69.3 %, penta-CBs: 17.2 %, hepta-CBs: 13.3 %). Regarding DDT pattern, p,p'-DDE was prevalent in all samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…As to the group of ToxRel PCBs, the most frequent congener was hepta-chlorinated PCB-170 (found in 91 % of the samples), while the highest median was that of PCB-118. The dominance of PCB-153, PCB-138, and PCB-118 is in agreement with other reports on marine organisms from the Adriatic (9,25,28,29,31,35), reflecting their high lipophilicity, stability, and persistence, which favour accumulation in aquatic animals. The overall levels are consistent with those recently found in fish species from the Adriatic Sea (13,15,29) and Atlantic coastal regions (27), and are higher than the values for the Black Sea (32), Catalan coast (31), Tunis (26), and Orbetello Lagoon (33) ( Table 3).…”
Section: Contaminant Levelssupporting
confidence: 92%
See 2 more Smart Citations
“…As to the group of ToxRel PCBs, the most frequent congener was hepta-chlorinated PCB-170 (found in 91 % of the samples), while the highest median was that of PCB-118. The dominance of PCB-153, PCB-138, and PCB-118 is in agreement with other reports on marine organisms from the Adriatic (9,25,28,29,31,35), reflecting their high lipophilicity, stability, and persistence, which favour accumulation in aquatic animals. The overall levels are consistent with those recently found in fish species from the Adriatic Sea (13,15,29) and Atlantic coastal regions (27), and are higher than the values for the Black Sea (32), Catalan coast (31), Tunis (26), and Orbetello Lagoon (33) ( Table 3).…”
Section: Contaminant Levelssupporting
confidence: 92%
“…The DDE/DDT ratios are often used as an indicator of recent DDT input into the environment. The prevalence of p,p'-DDE in this study (DDE/DDT>0.6 in more than 91 % of samples) is in line with the reports on DDT metabolites in fish species from other European and Mediterranean countries (24)(25)(26)(28)(29)(30)(31), and indicates that DDT in our study is mostly owed to historical use or remote sources and that it has not recently been used in agriculture. The obtained trend of the DDT isomers (DDE>DDT≈DDD) is consistent with the high chemical stability and long half-life of DDE in the aquatic environment in comparison to the parent DDT (25).…”
Section: Contaminant Levelssupporting
confidence: 92%
See 1 more Smart Citation
“…Due to their hydrophobic properties, POPs are easily incorporated into particulate organic matter (POM) where they are transported vertically from the surface water accumulating in the deep-sea environment. 1 As a result, POPs such as polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) have been ubiquitously detected in a range of deep-sea animals (PCBs 1–12,400 ng/g lipid weight and PBDEs 0.1–517 ng/g lipid weight) 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 and deep-sea sediments (PCBs <0.001–4 ng/g dry weight and PBDEs 0.05–0.3 ng/g dry weight). 11 , 13 , 14 , 15 Several studies have shown that the levels of POPs in the deep-sea environment can be higher than those recorded in shallow waters 16 and, as such, the deep sea is considered to be a potential sink for these persistent contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…They count the stocks or the structure of populations or describe its lifecycle in relation to its diet or genetic characteristics. Only one article authored by an Italian team from Bari University focuses on its possible contribution to ecotoxicology (see Storelli et al 2012 for DDT and PCBs). The other publications, while not focused on this species in particular, raise the question of its utility in assessing, along with others, the extent of chemical pollution (see Chahid et al 2014 for cadmium and lead off the coast of Morocco; Alcaro et al 2012 or Della Torre et al 2010 for chemical weapon residue in the Adriatic).…”
Section: Introductionmentioning
confidence: 99%